High pulse pressure is related to risk of type 2 diabetes mellitus in Chinese middle-aged females. (1st October 2016) - Zhang, Lu; Wang, Bingyuan; Wang, Chongjian; Li, Linlin; Ren, Yongcheng; Zhang, Hongyan; Yang, Xiangyu; Zhao, Yang; Han, Chengyi; Zhou, Junmei; Luo, Xinping; Hu, Dongsheng
Abstract: Background: To examine the association of risk of incident type 2 diabetes mellitus (T2DM) with high pulse pressure (PP) by sex. Methods: We performed a prospective cohort study of 12, 272 eligible participants (4664 males and 7608 females) without diabetes at baseline. Participants were classified as having normal PP (20–60 mm Hg) and high PP (> 60 mm Hg) at baseline. The analysis was further stratified by sex, quartiles of age and high PP categories. Results: During 6 years of follow-up, T2DM developed in 775 participants and the incidence was 10.57/1000 person-years. With PP 70 to 76 mm Hg, the multivariable adjusted hazard ratio (HR) (95% confidence interval) for incident T2DM in females was 1.722 (1.093–2.714) after adjustment for baseline age, smoking, alcohol intake, physical activity level and family history of T2DM, and 1.634 (1.037–2.575) after adjustment for the above factors and body mass index, waist circumference, blood lipid levels and fasting plasma glucose (FPG) category. After stratification by quartiles of age, for females aged 52 to 59, the multivariable adjusted HRs (95% CI) for high PP as compared to normal PP were 2.263 (1.517–3.377) and 2.140 (1.426–3.210) in different models. During follow-up, levels of FPG, fasting plasma insulin and homeostatic model assessment of insulin resistance index (HOMA-IR) were higher in females with higher than normal PP group, but β-cell function was impaired in the high PP group ( P < 0.05). Conclusion: High PP may be related to incident T2DM among female in China, especially women 52 to 59 years old.